Galactin-8 DNA methylation mediates macrophage autophagy through the MAPK/mTOR pathway to alleviate atherosclerosis - Bing Xia; Yan-lin Lu; Jin Peng; Jing-wei Liang; Fang-qin Li; Jiu-yang Ding; Chang-wu Wan; Cui-yun Le; Jia-lin Dai; Jie-Wang; Bing Guo; Jiang Huang (Scientific Reports)
Abstract DNA methylation modifications are an important mechanism affecting the process of atherosclerosis (AS). Previous studies have shown that Galectin-8 (GAL8) DNA methylation level is associated with sudden death of coronary heart disease or acute events of coronary heart disease. However, the mechanism of GAL8 DNA methylation and gene expression in AS has not been elucidated, prompting us to carry out further research on it. ApoE-/- mice were used to establish an atherosclerosis model, and DNA methylation inhibitor DO05 and MAPK/mTOR inhibitor UO126 were used for intervention. Pyrosequencing was used to detect changes in GAL8 DNA methylation levels of the mouse aorta between groups. ROC curve analysis was performed to assess the relationship between GAL8 DNA methylation and atherosclerosis. Aortic staining with hematoxylin and eosin (H&E) was used to observe the aortic intima, plaque area, and characteristics of secondary lesions within the plaque. Oil Red O staining was used to detect lipid deposition in mouse arterial plaques or macrophages. Movat staining was used to detect the number of foam cells in the plaque. Immunohistochemistry (IHC) and Western blot were used to quantify the localization and expression levels of DNA methyltransferase1 (DNMT1), GAL8, MAPK/mTOR pathway proteins, Light Chain3 (LC3), Beclin1, Sequestosome1 (p62), Tumor Necrosis Factor-α (TNF-α), and other proteins. Immunofluorescence (IF) was used to detect the fluorescence intensity of GAL8, LC3, Monocyte chemoattractant protein-1(MCP-1), and other proteins. Detection of autophagosomes in macrophages by transmission electron microscopy was also performed. The foam cell model was induced with human monocytes (THP-1) and co-cultured with foam cells using siRNAs targeting GAL8, DO05, and UO126. The level of DNMT1 was detected by Western blot; Oil red O staining was used to detect lipid deposition in foam cells in each group, and the localization and expression levels of GAL8, MAPK/mTOR pathway proteins, LC3, Beclin1, p62, and TNF-α were quantitatively determined by Western blot. Immunofluorescence (IF) was used to detect the fluorescence intensity of GAL8, MAPK/mTOR pathway protein, LC3, p62, TNF-α, and other proteins. The GAL-8 promoter region harbors six CpG sites susceptible to DNA methylation. Following DNMT1 inhibition, the DC05 group displayed a significant decrease in methylation across all six CpG sites compared to the C57 and AS groups. Conversely, the UO126 group exhibited increased methylation at the first three CpG loci relative to the AS group. ROC curve analysis revealed GAL8 DNA methylation as an independent risk factor for atherosclerosis: GAL8, along with inflammation-related proteins MCP-1, MMP9, and TNF-α, were upregulated in the mouse lesion group, while expression of autophagy-related proteins LC3 and Beclin1 was downregulated. Additionally, phosphorylated MAPK/mTOR pathway proteins were detected in the mouse model of atherosclerosis. After inhibiting the methylation level of GAL-8 DNA, the expression of GAL-8 was up-regulated, macrophage autophagy was inhibited, inflammation was increased, and atherosclerotic lesions in mice were aggravated. After direct inhibition of the activity of the MAPK/mTOR pathway, macrophage autophagy was further weakened, the inflammatory response was further aggravated, and the atherosclerotic lesions of mice were further aggravated. After the specific knockdown of GAL-8 using siRNA GAL-8 using foam cells, the above phenomenon was reversed, macrophage autophagy was promoted, the inflammatory response was reduced, and the degree of atherosclerosis was alleviated. The degree of GAL8 DNA methylation is related to the progression of atherosclerosis, and its hypomethylation can aggravate atherosclerotic lesions. The mechanism may be through the regulation of MAPK/mTOR pathway to slow down the autophagy of macrophages, and then aggravate the inflammation in plaques. Targeting GAL8 DNA methylation may be a new target for the diagnosis and treatment of atherosclerosis.